INOVASI PEMILIHAN KEPALA DESA BERBASIS E-VOTING DI DESA BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Deri Indrawan; Dadang Mashur (ADMIN: Jurnal Administrasi Negara, 2023)
The existence of a breakthrough innovation in this case is very important because in addition to maintaining the smooth running of the democratic party, it can also maintain public confidence in the voting results in general elections, regional head elections, and village head elections. In addition, the importance of innovation in village head elections is due to the development of technology, in which elections which are usually done manually can be done electronically. E-Voting has the meaning of using computer technology in the implementation of voting or voting. E-Voting is essentially an electronic (digital) voting process starting from the voter registration process, holding elections, counting votes, and sending vote results. The implementation of E-Voting is expected to overcome the problems that arise from conventional elections. Batu Gajah Village is one of the villages that was elected using the village head election with the Electronic Voting system, this is a very extraordinary appreciation for Batu Gajah village because it is one of 3 villages out of 62 villages that participated in the simultaneous Pilkades implementation, some of which still use the manual system, while Batu Gajah village was chosen to try the Electronic Voting system in the implementation of village head elections. The purpose of this study is to find out how the E-Voting election innovation can work. This study uses a purposive sampling technique with a qualitative research type with a descriptive approach, the required data such as primary data and secondary data obtained through interviews and documentation are then analyzed based on research problems. The results of this study indicate that the innovation of the Batu Gajah village head election through E-Voting can run well with supporting factors, namely human resources, facilities and infrastructure, and time management.